Carbon supported nickel-phthalocyanine/MnOx as novel cathode catalyst for microbial fuel cell application. (7th September 2017) - Tiwari, B.R.; Noori, Md. T.; Ghangrekar, M.M.
Abstract: Performance of microbial fuel cells (MFCs) with carbon supported nickel phthalocyanine (NiPc)MnOx composite (MFC-1) and nickel phthalocyanine (MFC-2) incorporated cathode was compared with a control MFC with non-catalysed carbon felt as cathode (MFC-3) and MFC-4 having Pt on cathode (as benchmark reference control). MFC-1 exhibited power density of 8.02 Wm −3, which was four folds higher than control MFC-3 (2.08 Wm −3 ) and 1.14 times higher than MFC-2 (6.97 Wm −3 ). Coulombic efficiency of 30.3% obtained in MFC-1 was almost double of that obtained for control MFC-3 and it was 5.4% lesser as compared to MFC-4 (35.7%). Linear sweep voltammetry study of cathodes revealed that NiPc-MnOx could enhance the electrocatalytic activity of oxygen reduction reaction (ORR) in comparison to control cathode. However, the power recovery from MFC-1 was noted little lower than what obtained from MFC-4 (10.58 Wm −3 ), however the cost normalized power was two times higher than Pt catalyst on cathode. Thus, NiPc-MnOx based catalyst developed in this study has potential to enhance ORR in cathodes of MFCs in order to harvest more power. Highlights: NiPc-MnOx was tested as cathode catalyst in MFC. Doping of MnOx on NiPc skeleton improved the electrochemical property. Power recovery from MFC with NiPc-MnOx was four folds higher than control MFC. Two fold increment in CE in MFC with NiPc-MnOx catalyst as compared to control MFC.